A DIACHRONIC ANALYSIS AND THEORETICAL FRAMEWORK FOR SOCIAL-EMOTIONAL LEARNING (SEL) IN LANGUAGE TEACHING - Abdullayeva Munojot Mukhtorovna, (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2026)
Social-Emotional Learning (SEL) has transitioned from a peripheral concern of moral philosophy to a central pillar of modern educational psychology and Second Language Acquisition (SLA). This article provides a comprehensive exploration of SEL, beginning with a diachronic analysis of its evolution—from the philosophical roots of character education to the contemporary era of neuroscientific validation. Subsequently, it synthesizes this historical context with the theoretical foundations of language teaching, arguing that SEL is a foundational necessity for achieving communicative competence. By bridging the gap between historical pedagogical shifts and modern frameworks like Krashen’s Affective Filter, Vygotsky’s Sociocultural Theory, and Goleman’s Emotional Intelligence, this paper posits that the integration of SEL into language education is essential for fostering holistic learner development in an increasingly interconnected world.